SOSIALISASI PEMBINAAN KELUARGA MASLAHAH KAMPUNG SRIWIJAYA MATARAM SEBAGAI BENTUK ANTISIPASI MENINGKATNYA ANGKA PERCERAIAN DI KABUPATEN LAMPUNG TENGAH - Arrasyid, Husain Fadhil; Hidayat, Efrizal; Anam, Khoirul; Choirunnisa, Silvi; Wati, Kurnia (ABDI MAKARTI, 2024)
The family is a very important basis for forming a strong Muslim society with integrity. Apart from that, it is the smallest part of society that determines progress or decline, therefore a strong family concept is needed, which is in accordance with Indonesia's diverse and tolerant society. The complex problems that occur in the Sriwijaya Mataram Village community are family problems due to economic factors and lack of knowledge about the law. This causes the divorce rate to soar. Based on the phenomena that occur in society, students carry out Socialization for the Development of the Maslahah Family in Sriwijaya Mataram Village using the Participatory Action Research (PAR) method or Participatory Action Research, namely a process of observation, socialization, then coaching. This socialization can convince the community that marriage must be prepared from pre-wedding to post-wedding, and solutions to family problems no matter how small must be immediately sought, in this way the concept of the maslahah family can be implemented, so that it is hoped that the target village community can become an example for other related areas. understanding of the laws that apply in Indonesia.